Plato’s Theory of the Arts in the Gorgias and in the Republic - Schmid, Walter Thomas (Revista Archai, 2020)
This paper examines Socrates’ theory of the arts in the Gorgias and in the Republic. It shows how that theory changes, as the discussion takes focus first in relation to moderation, then to justice, where it is tied to the idea of a techne of rule, to notions of virtuous work and civic health, and to five levels of ‘art’ represented in the cave. It argues that both Socrates’ vision of a scientific and benevolent political art and Thrasymachus’ sophistic theory of tyrannical rule are undercut in the dialogue, the former by doubts concerning the epistemic closure it seems based on, the latter by the tyrant’s character, which impels him toward self-destructive government.